PENGARUH ENDORPHINE MASSAGE TERHADAP PENURUNAN INTENSITAS NYERI PUNGGUNG IBU HAMIL DI KLINIK JULIANA TANJUNG MORAWA - Dwi Handayani; Juliana .; Raisha Octavariny; Desideria Yosepha Ginting (JURNAL KEBIDANAN KESTRA (JKK), 2021)
Pregnancy is something that is happy for husband and wife, but sometimes complaints arise during pregnancy, one of which is back pain. Back pain that occurs in the third trimester of pregnancy along with the enlargement of the uterus with the growth of the fetus, the center of gravity of the body is more inclined forward, so that pregnant women must adjust their position to maintain balance, as a result the body will pull the back so that it is more backward, the lower spine is more curved and shortened spinal muscles (Diah Galuh, 2017). This type of research used in the study is that Quasi- Experiment with design design One Group pretest posttest. The population of the research this isthe whole mother conceive that there are visits Antenatal care at the Clinic Juliana, Mechanical taking a sample of this is using purposive sampling as many as 18 people, before done Endorphins Massage is a total of 8 pregnant women (44.4%) experienced moderate pain scale and as many as 10 pregnant women (55.6%) experienced severe pain scale. Meanwhile, the frequency of back pain in pregnant women after this is done Endorphin Massage as many as 12 pregnant women (66.7%) experienced mild pain and as many as 6 pregnant women (33.3%) experienced moderate pain . Based on the results of analysts by using the test chi Square , obtained p-value ( 0.002), this means that there is the influence of Endorphins Massage to decrease the intensity of pain back mother pregnant at clinic Juliana